Exchange rates and prices: Evidence from the 2015 Swiss Franc appreciation - Raphael A. Auer; Ariel T. Burstein; Sarah M. Lein-Rupprecht (University of Basel, Center of Business and Economics (WWZ), 2018)
The removal of the lower bound on the EUR/CHF exchange rate in January 2015 provides a unique setting to study the implications of a large and sudden appreciation in an otherwise stable macroeconomic environment. Using transaction-level data on non-durable goods purchases by Swiss consumers, we measure the response of border and consumer retail prices to the CHF appreciation and how household expenditures responded to these price changes. Consumer prices of imported goods and of competing Swiss-produced goods fell by more in product categories with larger reductions in border prices and a lower share of CHF-invoiced border prices. These price changes resulted in substantial expenditure switching between imported and Swiss-produced goods. While the frequency of import retail price reductions rose in the aftermath of the appreciation, the average size of these price reductions fell (and more so in product categories with larger border price declines and a lower share of CHF-invoiced border prices), contributing to low pass-through into import prices.
Keywords: D4; E31; E50; F31; F41; L11; 330; large exchange rate shocks; exchange rate pass-through; invoicing currency; expenditure switching; price-setting; nominal and real rigidities; monetary policy